Global Neuroblastoma Network: An international multidisciplinary neuroblastoma tumor board for resource‐limited countries. Issue 4 (27th January 2022) - Matthay, Katherine K.; Hylton, Jennifer; Penumarthy, Neela; Khattab, Mohammed; Soh, Shui Yen; Nguyen, Hoa Thi Kim; Alcasabas, Ana Patricia; Fawzy, Mohammed; Saab, Raya; Khan, Muhammad Saghir; Ghandour, Khalil; Chantada, Guillermo; et al.
Abstract: Background: Tumor boards are part of standard care of patients with complex cancers, but appropriate multidisciplinary expertise and infrastructure are often not available in low‐ and middle‐income countries (LMIC) for pediatric cancers, such as neuroblastoma. Our goal was to review results of a Global Neuroblastoma Network (GNN) tumor board accessible to LMIC. Methods: De‐identified clinical cases presented via internet conference during a weekly GNN virtual tumor board from 2010 through 2020 were evaluated in a standardized format, including diagnostic imaging, pathology, therapy information, resource limitations, and questions for discussion. Information summarized included the presentations, a survey of the impact on care, and a resource questionnaire. Results: Registered GNN participants included 575 individuals from 77 countries, with a median of 39 participants per session. Total 412 cases were presented from 32 countries, including 351 unique neuroblastoma patients, 52 follow‐up cases, and nine non‐neuroblastoma diagnoses. Twenty‐eight educational sessions were presented. Limited critical resources for diagnostics and staging of cases included MYCN analysis (54.7%), metaiodobenzylguanidine (MIBG) scans (38.7%), and International Neuroblastoma Pathology Classification (49%). Therapies were also limited, with markedly decreased use of radiation and autologous stem cell transplant for high‐risk cases, and no availability of anti‐GD2 antibody in LMIC. Limited sampling with a post‐presentation survey showed that 100% found the GNN helpful, and 70% altered the care plan based on the discussion. Conclusion: This report shows the utility of an international tumor board for LMIC focused on a challenging solid tumor where local expertise may be limited, with international multidisciplinary expert participation and educational sessions.